Regionalna integracja ekonomiczna a dobrobyt gospodarki światowej - Rynarzewski, Tomasz (Economic Regional Integration and Condition of the World Economy, 2005)
An observed inconsistency between liberalization and neoprotectionism in a contemporary global economy can be also transferred to the field of the regional economic integration. The development of integration leads to removal of trade barriers inside the group of countries and maintaining the barriers with the third countries. Occurred static integration effects: creation and diversion and terms of trade effect influence global welfare in reverse direction. Theoretically, a net result of these effects is difficult to evaluate unequivocally. Considered circumstances of positive regional integration influence global welfare, which include Krugman, Kemp-Wan and „natural" trade partners conceptions, and come under criticism with regard to a strong dependence of conclusion from established presumptions. However, from a dynamic point of view, the benefits of the regional economic integration development should have a positive impact on global welfare, which will be strengthened by observed, already in the reality, a process of regional groups' enlargement connected with progressing multilateral trade liberalization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 324-339